Social Support and Community Integration in Users of Brazil’s Basic Social Protection Policy - Pizzinato, Adolfo; Soares de Almeida-Segundo, Damião; Pagnussat, Esequiel; Almeida Weber, João Luis; Bones Rocha, Katia (Psykhe, 2021)
<div id="titleAndAbstract" style="text-align: justify; margin-right: 20px; font-size: 12px; color: #666666; font-family: Arial, Helvetica, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">This study aimed to verify how community participation, family support, and sociodemographic variables relate to community integration. Participants were 201 individuals from the Brazilian state of Rio Grande do Sul, residing in the cities of Porto Alegre and Esteio, who benefited from a basic social protection program, PAIF (Proteção e Atendimento Integral à Família). The non-probability sample was mainly composed of low socioeconomic status women with a low educational level who were beneficiaries of social financial support programs. The research protocol comprised the Inventory of Family Support Perception, the Questionnaire of Community Social Support, and questions about sociodemographic characteristics. Correlation of PAIF participation duration with community integration was weak (r = 0.145, p < 0.05). A linear regression model showed that age (β = 0.323, p < 0.001), the monetary value of the benefit (β = 0.224, p = 0.002), and community participation (β = 0.234, p = 0.002) were predictors, accounting for 30.5% of the variance of community integration. Results indicate that, as people age in the community, they increase their integration. The amounts received by each family probably affect community integration because they expand access to community spaces and public services. Individuals with greater community support tools felt more welcome in the community network. Additional studies are needed to provide evidence for the effectiveness of social integration and health promotion interventions.